Synthesis of the cerium doped Gd3Al3Ga2O12-based glass nanoceramics: Luminescence and optical absorption properties. (April 2023) - Buryi, Maksym; Tratsiak, Yauhen; Trusova, Ekateryna; Babin, Vladimir; Paterek, Juraj; Kučerková, Romana; Remeš, Zdeněk; Hájek, František; Landová, Lucie; Drahokoupil, Jan; Chertopalov, Sergii
Abstract: Cerium doped gadolinium gallium aluminum garnet (Gd3 Al3 Ga2 O12, GAGG) was synthesized in the glass ceramics form by the crystallization from Gd2 O3 –Al2 O3 –Ga2 O3 –SiO2 –CeO2 glass in the following weight proportion: 101 : 26: 47 : 25: 1. The spatial distribution and incorporation of Ce into the GAGG ceramic grains as well as the luminescence and scintillation performance are studied carrying out correlated experiments of photo-, radio- and cathodoluminescence including decay kinetics as well as energy dispersive X-ray spectroscopy combined with scanning electron microscopy. Optical absorption features were investigated using photothermal deflection spectroscopy. Cerium stays within the material mostly in the Ce 3+ charge state. Its distribution in the bulk of the sample exhibits irregular trend indicating the tendency to coalesce in the middle. Highlights: The GAGG:Ce glass nanoceramics was fabricated. Spatial distribution of Ce 3+ in the batch of the glass nanoceramics was observed. Hole trapping processes affect the luminescence in GAGG:Ce glass nanoceramics.